Long-chain omega-3 fatty acids and the brain: a review of the independent and shared effects of EPA, DPA and DHA - Dyall, Simon C. (Frontiers in Aging Neuroscience, 2015)
Omega-3 polyunsaturated fatty acids (PUFAs) exhibit neuroprotective properties and represent a potential treatment for a variety of neurodegenerative and neurological disorders. However, traditionally there has been a lack of discrimination between the different omega-3 PUFAs and effects have been broadly accredited to series as a whole. Evidence for unique effects of eicosapentaenoic acid (EPA), docosahexaenoic acid (DHA) and more recently docosapentaenoic acid (DPA) is growing. For example, beneficial effects in mood disorders have more consistently been reported in clinical trials using EPA; whereas, with neurodegenerative conditions such as Alzheimer’s disease, the focus has been on DHA. DHA is quantitatively the most important omega-3 PUFA in the brain, and consequently the most studied, whereas the availability of high purity DPA preparations has been extremely limited until recently, limiting research into its effects. However, there is now a growing body of evidence indicating both independent and shared effects of EPA, DPA and DHA. The purpose of this review is to highlight how a detailed understanding of these effects is essential to improving understanding of their therapeutic potential. The review begins with an overview of omega-3 PUFA biochemistry and metabolism, with particular focus on the central nervous system, where DHA has unique and indispensable roles in neuronal membranes with levels preserved by multiple mechanisms. This is followed by a review of the different enzyme-derived anti-inflammatory mediators produced from EPA, DPA and DHA. Lastly, the relative protective effects of EPA, DPA and DHA in normal brain aging and the most common neurodegenerative disorders are discussed. With a greater understanding of the individual roles of EPA, DPA and DHA in brain health and repair it is hoped that appropriate dietary recommendations can be established and therapeutic interventions can be more targeted and refined.